Proposta de uma nova concepção de um estabilizador de lkVA de alto rendimento - Sanhueza, Sergio Manuel Rivera (2002)
The voltage sag is a constant event on power distribution system networks, this makes mandatory for electricity authorities to have a high levei information on its electrical system. Preventive measures should also be taken by its consumers, since it is impossible for the authority to eliminate completely such occurrences. One of the altematives for the consumers it is the installation of equipment which has the task to keep the voltages at accepted leveis. To accomplish such demand for this equipment, the electrical and electronic industry developed a variety of types of voltage stabilizing equipment. One of the main types of such equipment is the stabilizer with a tuning transformer which has the disadvantages of being expensive, with a high volume and having a high energy consumption. With the task of replace this equipment, this dissertation presents a proposal of a new Low Cost Electronic Voltage Stabilizer, with a reduced physical dimensions and mainly a low electrical energy consumption.